Practical Aspects of Declarative Languages 15th International Symposium, PADL 2013, Rome, Italy, January 21-22, 2013. Proceedings - Sagonas, Kostis; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed post-proceedings of the 15th International Symposium on Practical Aspects of Declarative Languages, PADL 2013, held in Rome, Italy, in January 2013, co-located with POPL 2013, the 40th Symposium on Principles of Programming Languages. The 17 revised papers presented were carefully reviewed and selected from 33 submissions. The volume features original work emphasizing new ideas and implementation techniques for all forms of declarative concepts, including functional, logic, and constraints.
A Library for Declarative Resolution-Independent 2D Graphics -- Analysing the Entire Wikipedia History with Database Supported Haskell -- LogicObjects: Enabling Logic Programming in Java through Linguistic Symbiosis -- A Declarative Compositional Timing Analysis for Multicores Using the Latency-Rate Abstraction -- Supporting Pruning in Tabled LP -- A Portable and Efficient Implementation of Coinductive Logic Programming -- Formalizing a Broader Recursion Coverage in SQL -- A Declarative-Friendly API for Web Document Manipulation -- Implementing Equational Constraints in a Functional Language -- On the Efficient Implementation of Mode-Directed Tabling -- The Generalized Intensional Transformation for Implementing Lazy Functional Languages -- Terminyzer: An Automatic Non-termination Analyzer for Large Logic Programs -- Integrative Functional Statistics in Logic Programming -- Reversible Language Extensions and Their Application in Debugging -- proSQLite: Prolog File Based Databases via an SQLite Interface -- Dependently Typed Web Client Applications: FRP in Agda in HTML5 -- Parallel Performance of Declarative Programming Using a PGAS Model.
Keywords: Computer science; Software engineering; Logic design; Computer Science; Programming Languages, Compilers, Interpreters; Programming Techniques; Logics and Meanings of Programs; Software Engineering